Implementasi Satua Sebagai Penguatan Kearifan Lokal Pada Lingkungan Multikultural Di Kelas X SMA Taman Rama Jimbaran Kabupaten Badung - Ida Ayu Putu Asti Pratiwi; Ida Ayu Tary Puspa; I Made Dian Saputra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The purpose of this research is the implementation of the learning of Bali Language especially about satua Bali as one very important aspect in as a strengthened point for local wisdom of Balinese culture in multicultural environment. This is a qualitative research, where the primary data is used as the main data based on the result of online observation, interview and questioner results. While the supporting data is achieved from the literature, result of previous research, and all the relevant references about the title of the research. The decision about the interviewer is done using purposive sampling technique. The data collecting was done by using observation, questioner, interview techniques, literary studies and documentation study. After data is collected, it is analyzed by reducing, classifying and making the summary. The results of the research can be stated as follows: (1) The learning process of satua Bali as a strengthened point for local wisdom is done by preparing the syllabus and lesson plan before implementing the lessons. Online learning process consists of three activities those are initial activity, main activity and closing activity. (2) The factors that influence students, understanding of satua Bali as a strengthened point for local wisdom are from internal factors for learning of the students those are the eagerness of students to study, students’ language ability, students’ source of learning and the environment. The external factors are interactions, knowing and solving students’ difficulties in learning and lack of periods for the students. (3) The strategy used in satua Bali learning process as a strengthened point for local wisdom are asking the teacher, discus with the classmates, repetition in reading the text carefully, pay attention properly, finding and writing the meaning of each word, watching the video of masatua Bali, and preparing oneself better.